Crianças com implante coclear: implicações linguísticas - Lynce, Sofia (2017)
The present exploratory study aims at exploring expressive linguistics abilities of cochlear-implanted children by testing spontaneous speech samples. For this purpose, Mean Length of Utterance in words will be measured and the productive use of single grammatical morphemes will be analysed. We analysed the spontaneous speech of three deaf Portuguese children with cochlear implants and three normal-hearing children paired case by case, taking into account the chronological age, gender and parental education. Cochlear-implanted children produced on average less than 2 words per utterance than normal hearing children. In morphology, cochlear implanted children from the sample were not capable to produce irregular plural formatives and to make productive use of inflectional morphemes on main verbs for the subjunctive and imperative modes. In general, the grammatical progress seems to be slower for cochlear-implanted children when compared to their hearing peers. Nevertheless, an earlier implantation, longer implant use and a bilateral implantation seem to bring benefits for the child’s spoken language.